Influence of Product Variation, Consuming Culture, and Reference Group on Consumer Behavior of Raja Kebab Products Rantauprapat - January Mendrofa; Elida Florentina Sinaga Simanjorang; Elvina Elvina (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2023)
From the results of this study, it can be concluded that this study aims to look at the involvement of the variables analyzed and see how much influence product variations, consumption culture, and reference groups have on consumer behavior in consuming Raja Kebab Rantauprapat products. In this study, researchers used quantitative research methods, The population in this study were buyers of Raja Kebab Rantauprapat products, namely as many as 50 people. The data in this study were processed using the SPSS 24 application with multiple linear regression tests. The results showed that partially or by T-test the variable Product Variation has a positive and significant effect on consumer behavior, this can be seen from T count 6.535 > T table 2.012 with a sig value of 0.000 < 0.05. The consumption culture variable has a positive and significant effect on consumer behavior, this can be seen from T count 8.437 > T table 2.012 with a sig value of 0.000 < 0.05. The Reference Group variable has a positive and significant effect on consumer behavior, this can be seen from T count 7.218 > T table 2.012 with a sig value of 0.000 <0.05. Meanwhile, simultaneously or F test the variable product variation, consumptive culture, and reference groups have a positive and significant effect, this can be seen from the F count 63.167 > 2.47 F table with a sig value of 0.000 < 0.05.